Pernan Advokat Dalam Memberikan Bantuan Hukum Kepada Masyarakat Dalam Perspektif Hak Asasi Manusia - Abdau Abdi Chaniago; Mahdi Nasution; Fauziah Lubis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Legal aid has an important position in every criminal, civil and state administrative justice system, including in Indonesia. The concept of legal aid relates to a person's rights to exercise these rights, therefore legal aid is carried out by legal experts and experienced people in order to carry out their profession. Legal aid is carried out by legal aid providers who are oriented towards noble values, namely the humanitarian aspect to fight for human rights to live in prosperity and justice. This paper aims to find out the role of advocates in law enforcement and to find out the obstacles they face in upholding the law, especially in defending their clients in the Pemko Medan area. Advocates in Pemko Medan, especially those who are members of the Indonesian Advocates Association Organization (AAI). Keywords:: Advocate, Legal Aid, Human Rights